Implementasi Makna Immanuel dalam Bahasa Jawa dengan Konsep Makna “Manunggaling Kawula Gusti” dalam Islam Tasawuf - Firmansah, Endik; Simon, Simon (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The Javanese Bible has a slightly different translation from other translations for the meaning of the word Immanuel. In particular, this difference can be seen when comparing the meaning of Immanuel in Javanese and the meaning of Immanuel in Indonesian. What is interesting is that the translation in Javanese for the word Imanuel has similarities with the sentence